1999
DOI: 10.1111/j.1365-2141.1999.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial serum thrombopoietin levels in a pregnant woman with essential thrombocythaemia

Abstract: Thrombopoietin (TPO) is a ligand for c-mpl, which regulates the differentiation and maturation of megakaryocytes. Essential thrombocythaemia (ET) is a clonal myeloproliferative disorder. It has been reported that the platelet count declines during pregnancy in ET patients. We examined serial changes in the serum TPO level during the course of pregnancy in a patient with ET. The serum TPO level showed significant negative correlation with the platelet count. Although it mimicked the normal feed back system, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The cause of this phenomenon is unclear but may be similar to that in normal pregnancy, in which platelet counts typically decrease by 10±15% of the pre-pregnancy level from 11 to 15 wk of gestation to 36±40 wk (57,58). Other possible mechanisms include an increase in platelet consumption (17), a hormonal response (45), placental or fetal production of a factor that reduces platelet production (54), and a cytokine-mediated decrease in megakaryocyte number (56).…”
Section: Discussionmentioning
confidence: 98%
“…The cause of this phenomenon is unclear but may be similar to that in normal pregnancy, in which platelet counts typically decrease by 10±15% of the pre-pregnancy level from 11 to 15 wk of gestation to 36±40 wk (57,58). Other possible mechanisms include an increase in platelet consumption (17), a hormonal response (45), placental or fetal production of a factor that reduces platelet production (54), and a cytokine-mediated decrease in megakaryocyte number (56).…”
Section: Discussionmentioning
confidence: 98%
“…It remains unknown whether the platelet count will decrease after some time without Case Reports in Hematology treatment if it rebounds. According to our searches in the English literature, some reports indicate that no particular cytoreductive therapy was required after delivery, whereas other reports describe cases in which patients were treated for a rebound of platelet count [14][15][16][17][18]. Sakai et al reported a case in which the platelet count increased to ≥1000 × 10 9 /L within 3 months after delivery and another case in which the platelet count increased to ≥800 × 10 9 /L within 2 months after delivery.…”
Section: Discussionmentioning
confidence: 99%